CORRELATION EXTREMAL PRINCIPLE OF OBJECT DETECTION ON GROUND SURFACE - Mukhina, Maryna (Proceedings of National Aviation University, 2013)
Features of correlation extremal principle for detection of ground objects are considered for visual surveillance. The method of phase correlation is researched and variants of its optimization are proposed.